4 months ago
Last edited at 7:20PM on 8/29/2013
expand everything first. -6(6x-4) = -36x+24. -2(-7-6x)= = 14+12x. so the new equation is -36x+24+14+12x = -34. move the term with 'x' on your left-hand side, and the other to your right-hand side. moving 24 and 14 to your LHS will make both of them -24 and -14. it will be -36x+12x = -34-24-14. solve it, -24x=-72. so x=-72/-24 =3.
The value of x is 3. To find the value, you will have to expand the brackets by multiplying the numbers in the brackets by the ones in the bracket. You will get -36x+24+14+12x = -34. Then, you will collect the like terms and substitute to get 3.